Based on telling stories, the communication problems encountered by supervisors through face to face supervision - Özmen, Fatma; Özdemir, Tuncay Yavuz (My University, 2012)
Supervision which is one of the important processes of educational management, aims generally to develop human resources, and the most effective means of it is communication. To mention of an effective supervision, the presence of effective communication is inevitable. The consequences of several researches done in Turkey, reveal that various communication problems have been witnessed during supervisory process and effectiveness has not been provided adequately. The aim of this research is, based on the stories told by the supervisors to determine the communication problems between supervisors and supervisees, during supervisory process and to develop recommendations in the frame of the premises of contemporary supervision. In this study, the supervisors were required to tell stories related to the communication problems witnessed during the supervisory process. The stories were written down, irrelevant ones were eliminated and then 20 stories were included into the research scope. The stories were examined within the frame of literature and the themes were coded. Therefore the issues related to communication problems were detected. According to the obtained results some recommendations were made towards lessening communication problems.
Anlatilan öykülere dayali olarak, denetçilerin denetlenenlerle yüz yüze iletişimlerinde yaşadiklari sorunlar